Bermain Terapeutik Puppet Play sebagai Intervensi untuk Menurunkan Kecemasan pada Anak saat Hospitalisasi - Devi Tirta Ningrum; Dessie Wanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze various types of puppet play to reduce children's anxiety levels while hospitalized. The method used is a systematic review through the Proquest database, Scopus, Science Direct, and Google Scholar. The selected articles were assessed for quality with the guidance of the Joanna Briggs Institutes (JBI). The results showed that from 11 review articles, it was revealed that playing puppet play effectively reduced children's anxiety during hospitalization, and the range of children given pain reduction strategies was 3-19 years. In conclusion, therapeutic puppet play can effectively reduce stress in children who experience hospitalization. Keywords: Children, Playing with Puppets, Hospitalization